Media Usage, Health Literacy, Health Anxiety, and Health Behaviors of University Students During the COVID-19 Pandemic - Dilek Demirtepe-saygılı; Elif Eşiyok; Eda Turancı (Türkiye İletişim Araştırmaları Dergisi)
Living with the pandemic influenced people’s lifestyles and health behaviors as well as their use of media.The aim of this study is to investigate the level of change in health behaviors of university students duringthe COVID-19 pandemic. The changes in health behaviors refer to changes of mainly eating and exercisebehaviors to stay healthy. In this study, media use, health literacy and health perception are the determinantsof change in health behaviors; health anxiety and healthy living skills are considered as mediating variables.Questionnaires were filled in by 392 university students in Ankara, Turkey within the second month ofthe pandemic. According to the findings, as the levels of positive perception of health, health literacy level,health anxiety level, and healthy life skills increase, the level of change in health behavior increases. Thepath analysis revealed that more positive perceptions of health and higher levels of health literacy are relatedto higher levels of change in health behaviors through the mediation of healthy life skills. In addition, theuse of Twitter increases health anxiety during the pandemic and results in a higher level of change in healthbehaviors. The findings help to better understand the motivations to change health behaviors for selfprotectionagainst the COVID-19 among university students.